First report of the invasive species and potential pest Zaprionus tuberculatus Malloch, 1932 (Diptera, Drosophilidae) in Pará, Brazil - Mendes, Mayara F.; Lamas, Carlos J. E. (Entomological Communications, 2025)
This paper reports the first occurrence of the potential pest Zaprionus tuberculatus Malloch, 1932 (Diptera, Drosophilidae) in the municipality of Belém, Pará, Brazil, specifically in the Amazon region at the vicinity of the Museu Paraense Emílio Goeldi. This report is crucial for collecting data on the geographic distribution and population growth of this invasive species, which will aid in the development of strategies for pest management programs. Furthermore, new points records for the invasive species in Brasília are presented for the first time, extending the spread of Z. tuberculatus across Brazil.